TINGKAT RESPONSIVITAS MEMODERASI: KARAKTERISTIK PEMERINTAH DAERAH, TEMUAN HASIL PEMERIKSAAN DAN KINERJA KEUANGAN - Ayunisa, Nirfa; Susetyo, Didik; Yusnaini, Yusnaini (Universitas Muhammadiyah Palembang, 2023)
This research aims to examine the influence of local government characteristics and audit findings on financial performance moderated by the level of local government responsiveness. The population and sample are 180 districts and cities. secondary data from inspection reports. Financial reports audited by BPKRI from 2017 to 2019. Panel data regression analysis technique, eviews data processing software with a random effect model. The results show that legislative measures, SPI weaknesses and non-compliance with statutory regulations have no effect on financial performance. Meanwhile, government size and level of wealth have a significant effect on financial performance. The level of responsiveness cannot strengthen the influence of legislative measures, SPI weaknesses and non-compliance with statutory regulations on financial performance. Meanwhile, the level of responsiveness can strengthen the influence of government size and the level of regional government wealth on financial performance.